2018
DOI: 10.11604/pamj.2018.30.176.14565
|View full text |Cite
|
Sign up to set email alerts
|

Les connectivites en milieu hospitalier à Lomé: étude rétrospective de 231 cas

Abstract: Le but de cette étude était de documenter le profil épidémiologique, clinique, thérapeutique et évolutif des connectivites en milieu hospitalier à Lomé. Il s'agissait d'une étude rétrospective descriptive menée du 1er Janvier 1993 au 31 Décembre 2012. Elle a porté sur les dossiers des malades ayant souffert d'une connectivite dans cinq services de dermatologie et de rhumatologie des centres hospitaliers de Lomé. Au cours de la période d'étude, nous avons recensé 231 cas de connectivites dans les cinq centres d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
2
9
1
2
Order By: Relevance
“…Our patients were mostly young women with an average age of 41 years. Our results agree with some studies in sub-Saharan Africa [4] [5]. The average time of diagnosis was 5 months.…”
Section: Discussionsupporting
confidence: 92%
“…Our patients were mostly young women with an average age of 41 years. Our results agree with some studies in sub-Saharan Africa [4] [5]. The average time of diagnosis was 5 months.…”
Section: Discussionsupporting
confidence: 92%
“…Our result was comparable to that found by Zouna in Mali [5] who reported a frequency of 2.05%. However, it was higher than those found by Teclessou et al [6] and Mijiyawa et al [4] in Togo who found a frequency of 0.19% and 0.20% respectively. In Senegal, Dioussé et al [3] reported a hospital prevalence of 0.29% over a 7-year study period at the department of dermatology.…”
Section: Discussioncontrasting
confidence: 59%
“…The hospital frequency of connective tissue diseases ranged from 0.20% to 1.60% [3] [4] [5] depending on the studies. The most frequent connective tissue diseases in the study done by Teclessou et al were systemic lupus erythematosus followed by scleroderma and rheumatoid arthritis [6], whereas in the study done by Dioussé et al they were represented by systemic lupus erythematosus followed by scleroderma and dermato-polymyositis [3].…”
Section: Introductionmentioning
confidence: 99%
“…Very little information is available about these diseases due to the scarcity of studies conducted on them, which might also be associated to the poor coverage of the African continent in terms of physician specialists and well equipped rheumatology and immunology units [5] [6]. In Togo, most studies on CIRD were monocentric and focused either on CIRDs in general or on one particular CIRD [7] [8] [9] [10] [11]. The scarcity of epidemiological surveys explains the fragmentary nature of the data currently available.…”
Section: Introductionmentioning
confidence: 99%